EMPOWER ENGLISH SONG BASED TEACHING TO ELEVATE VOCABULARY MASTERY OF EFL LEARNERS (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
The accessibility and popularity of English song in the teenagers facilitates them to be able to expand their English acquisition. Therefore, this research aims to validate whether English Song Based Teaching can boost vocabulary mastery of the students in two aspects namely meaning and use. This research utilized quantitative design in term of pre-experimental. Pre-test and post-test were conducted to gather the data. The research sample consisted of 15 students of class XI A of SMA Kristen Bala Keselamatan Palu. The finding demonstrates that the implementation of English song provides a significance impact on students' vocabulary mastery. The paired sample t-test supports this finding which a significance value of less than 0.05. It can be claimed that song-based teaching provides positive effects toward cognitive (vocabulary knowledge) and social aspect of language learning.
Keywords: English Acquisition; Pre-Experimental Design; Teenage Learners; Song-Based Teaching; Vocabulary Mastery